Pembelajaran Metode dan Evaluasi Filsafat di Stai Al Mashturiyah dalam Konteks Pendidikan Tinggi Islam - Miswan Ramadani; M. Nasir; Muawiyah Muawiyah; Putri Nurdiana; Rio Pratama (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the learning methods and evaluation of philosophy at STAI Al Mashturiyah within the context of Islamic higher education. The background of this research is the need to strengthen critical, reflective, and ethical thinking among students through philosophy learning that is relevant to Islamic values. The study aims to analyze how philosophy learning methods are implemented and how evaluation practices are applied in the classroom. This research employs a qualitative descriptive approach, with data collected through direct interviews with philosophy course lecturers and supported by academic documents. The findings indicate that philosophy learning at STAI Al Mashturiyah applies a combination of lectures, discussions, and question-and- answer methods, while evaluation is conducted through written assessments and process-based evaluations such as participation and presentations. These approaches contribute to the development of students’ analytical and argumentative skills. The study highlights the importance of integrating interactive learning methods and comprehensive evaluation systems to enhance the quality of philosophy education in Islamic higher education. The results have implications for improving pedagogical practices and strengthening the theoretical and practical foundations of philosophy learning in Islamic institutions.